Informatic prediction of Cheddar cheese flavor pathway changes due to sodium substitution. Issue 2 (9th December 2013) - Ganesan, Balasubramanian; Brown, Kelly
Abstract Increased interest in reduced and low sodium dairy foods generates flavor issues for cheeses. Sodium is partly replaced with potassium or calcium to sustain the salty flavor perception, but the other cations may also alter metabolic routes and the resulting flavor development in aged cheeses. The effect of some cations on selected metabolic enzyme activity and on lactic acid bacterial physiology and enzymology has been documented. Potassium, for example, is an activator of 40 enzymes and inhibits 25 enzymes. Currently, we can visualize the effects of these cations only as lists inside metabolic databases such as MetaCyc. By visualizing the impact of these activating and inhibitory activities as biochemical pathways inside a metabolic database, we can understand their relevance, predict, and eventually dictate the aging process of cheeses with cations that replace sodium. As examples, we reconstructed new metabolic databases that illustrate the effect of potassium on flavor‐related enzymes as microbial pathways. After metabolic reconstruction and analysis, we found that 153 pathways of lactic acid bacteria are affected due to enzymes likely to be activated or inactivated by potassium. These pathways are primarily linked to sugar metabolism, acid production, and amino acid biosynthesis and degradation that relate to Cheddar cheese flavor.